AKAD IJARAH MUNTAHIYAH BITTAMLIK PADA PEMBIAYAAN PROPERTI SYARIAH: ANALISIS HUKUM EKONOMI DAN FATWA DSN-MUI NO. 27/III/2002 - Badai Husain Hasibuan (Yurisprudentia: Jurnal Hukum Ekonomi, 2025)
This study examines the Islamic economic system with a focus on the Ijarah Muntahiyah Bittamlik (IMBT) contract as a form of financing that is widely used by Sharia Financial Institutions (LKS), especially in the property sector. This contract is a combination of the concepts of ijarah (lease rent) and tamlik (transfer of ownership) which is carried out after the lease period ends. IMBT is considered an alternative financing that is in accordance with sharia principles because it does not contain elements of riba like conventional financing. However, in practice, the implementation of this contract often raises problems, including incompatibility with the contract with the principles and terms of the contract, as well as deviations from the provisions in the DSN-MUI Fatwa No. 27/DSN-MUI/III/2002. One of the irregularities that occurred was the merger of the lease and sale and purchase contracts in one contract, which gave rise to elements of gharar and tasyabbuh with riba. This study uses a juridical normative method with three main approaches, namely the legislative approach, the conceptual approach, and the fatwa and doctrine approach. Data were obtained through literature studies and analyzed descriptively-analytically. The results of the study show that the Ijarah Muntahiyah Bittamlik contract has a legal duality, namely as a lease contract at the initial stage and a transfer of ownership contract at the end of the lease period. DSN-MUI Fatwa No. 27/DSN-MUI/III/2002 requires the separation between ijarah and tamlik contracts through promises (wa'd) that are not legally binding. However, practice in the field shows that Islamic financial institutions still combine the two contracts, and there is an imbalance of responsibility between banks and customers regarding costs and risks during the lease period. This harms the principles of justice ('adl) and balance (tawazun) in Islamic economic law. Therefore, improvements are needed in contractual aspects, regulations, and increased understanding of the essence of IMBT so that its implementation is truly in accordance with sharia principles.